1983
DOI: 10.1007/bf01805811
|View full text |Cite
|
Sign up to set email alerts
|

β‐Mannosidosis: Prenatal biochemical and morphological characteristics

Abstract: Caprine beta-mannosidosis, an autosomal recessive disorder of glycoprotein catabolism, as yet undetected in man, was expressed in a 96/150 day gestation goat fetus. Deficiency of plasma, kidney, brain, liver and skin fibroblast acidic beta-mannosidase activity was associated with the accumulation of tissue oligosaccharides. Characteristic lucent cytoplasmic lysosomal storage vacuoles were present in the brain, thyroid, kidney and other tissues. Axonal spheroids were present in the central nervous system. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Our assay conditions allowed the detection of ]3-mannosidase deficiency in the goat. Fibroblasts from an affected goat showed a clear deficiency (Table 1), confirming the results of Jones et al (1984). It is remarkable that 13-mannosidase activity in both fibroblasts and leukocytes of human origin is more than ten-fold higher.…”
Section: Panday Van Diggelen Kleijer and Niermeijersupporting
confidence: 85%
“…Our assay conditions allowed the detection of ]3-mannosidase deficiency in the goat. Fibroblasts from an affected goat showed a clear deficiency (Table 1), confirming the results of Jones et al (1984). It is remarkable that 13-mannosidase activity in both fibroblasts and leukocytes of human origin is more than ten-fold higher.…”
Section: Panday Van Diggelen Kleijer and Niermeijersupporting
confidence: 85%
“…ß-Mannosidase activity was measured using 4-methylumbelliferyl-ß-Z)-mannopyranoside as pre viously described [21], except where noted. Protein was determined by the method of Lowry et al [22] using human albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Age-matched twin male fetuses (V86, V87) were obtained from normal (non-carrier) parents to serve as MS received 26.4.85 Accepted 1.8.85 controls. V83 and V86, both males, were used in this investigation after studies of the [3-mannosidase activities in plasma, kidney, liver, brain, and skin fibroblasts revealed that V83 was affected and V86 was normal (Jones et al, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…This disease is characterized by a deficiency of [3-mannosidase activity in plasma (Healy et al, 1981;Cavanagh et al, 1982;Jones et al, 1984), tissue (Healy et al, 1981;Jones and Dawson, 1981) and skin fibroblasts (Jones et al, 1984) and by the tissue accumulation (Jones and Laine, 1981;Matsuura et al, 1981a) and urinary excretion (Matsuura et al, 1983) of oligosaccharides. Previous studies have revealed that [3-mannosidase deficiency is accompanied by the accumulation of the disaccharide, [3-mannosyl-(1-4)-N-acetylglucosamine (DS) and the trisaccharide, t3-mannosyl-[3-(1-4)-N-acetylglucosaminyl-(1-4)-N-acetylglucosamine (TS), in the tissues of affected prenatal (Jones et al, 1984) as well as neonatal Jones et al, 1983) goats. Furthermore, the detection of [5-mannosidase deficiency in the cultured skin fibroblasts of an affected fetus suggested the feasibility of prenatal detection of [~-mannosidosis (Jones et al, 1984), a disease not yet identified in man.…”
mentioning
confidence: 96%
See 1 more Smart Citation